The Effect of Egg-White Gradient and Incubation Time on Sex Separation for Semen Quality in Dorper Rams - Alwan, Mochamad Daffa; Sumaryadi, Mas Yedi; Saleh, Dadang Mulyadi; Setyaningrum, Agustinah; Rahayu, Sri (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2026)
Improving Dorper sheep meat production efficiency through sperm sex separation (sexing) technology using egg white gradients is an economical alternative, yet it is often hindered by the decline in post-freezing semen quality due to cold shock. This study was aimed to evaluate the effectiveness of combining egg white medium concentration gradients and incubation times on the quality of liquid and frozen-thawed semen. Using fresh semen from two Dorper rams (aged 24 months), this study employed a 2x3 Factorial Randomized Block Design (RBD) with four replications. Treatments consisted of two gradient levels (15:30% and 20:35%) and three incubation times (30, 45 and 60 minutes). The obtaimed data were analyzed using Analysis of variane and continued with Duncan's multiple range test if there were significantly differences betrweem treatments. Results showed that incubation time significantly affected (P<0.05) motility, viability and concentration. Specifically, the 15:30% gradient with 45 minutes of incubation proved to be the most optimal, yielding 51.25% post-sexing motility and 53.88% viability. This superiority persisted through the post-thawing stage, where this treatment recorded the highest motility (12.50%) and viability (14.25%). However, frozen semen values were generally low. Conversely, 60-minute incubation significantly reduced quality due to metabolic exhaustion, while the 20:35% gradient had excessive viscosity that hindered sperm penetration, drastically lowering the final concentration to 4.75 x 10⁷ cells/mL. Although fluctuations occurred, abnormality rates across all treatments remained below the 20% threshold. It is concluded that freezing techniques require evaluation, using a 15:30% egg white gradient with 45 minutes of incubation at 37°C is the best protocol in this study recommended for Dorper sheep sex separation, as it maximally maintains membrane integrity and sperm survival in both liquid and frozen phases.